Detection of sarcocystis in carcasses of small ruminant slaughtered in abattoir in Perak, Malaysia - Fazly Ann Zainalabidin (Syiah Kuala University, 2021)
Sarcocystis is a cyst forming intracellular protozoa with an obligatory two-host life cycle. The prey-predator relationships may result in muscular sarcocystis in intermediate host and intestinal sarcocystis in definitive host. The study on the parasites was conducted in abattoirs in Perak with the aim to detect the existence of sarcocystis in small ruminant from the slaughtered carcasses by digestion method and histological examination. A total of 90 fresh muscle samples from 30 goats were randomly collected commencing from March to August 2016. The result shows 23.33% (7 out of 30) of the animals were positive with sarcocystis microcyst with 20.00% (6 out of 30) and 13.33% (4 out of 30) by digestion method and histological examination, respectively. Most of the positive samples were detected from the thigh muscles by both diagnostic techniques. Among the positive animals, 14.29% (1 out of 7) of the animals were heavily infected in which microcyst were detected in the heart, esophagus and thigh muscle samples. No sarcocystis macrocyst were detected upon observation. Even though sarcocystis in small ruminant in this study was reported less than quarter of the samples, the presence of the parasites could not be ignore as it may infect the carnivorous animals. Provide thoroughly cooked meat to the animals will reduce the potential infection of the disease.